SYSTEMATIC LITERATURE REVIEW (SLR): "EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBASIS MEDIA DIGITAL DALAM PEMBELAJARAN SEKOLAH DASAR” - Hidayat, Wahyu; Saputra, Bagas; Zahra, Alya; Ruzaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian students' low achievement in PISA 2022 across mathematics, reading, and science reflects a fundamental and persistent challenge, one of which is the dominance of passive learning in elementary school classrooms. This study maps the extent to which Problem Based Learning (PBL) integrated with digital media can serve as a solution that is not merely promising in theory but proven effective in practice. Using a Systematic Literature Review (SLR) approach, this study analyzes 20 articles screened from 200 search results via Google Scholar and Publish or Perish, covering publications from 2021 to 2025. The two main foci examined are its influence on cognitive learning outcomes and the dimensions of student engagement most significantly affected. Findings show that digital media-based PBL consistently improves student learning outcomes across subjects, including Mathematics, Science, IPAS, and Bahasa Indonesia. Beyond score improvements, digital media such as animations, Kahoot, and Wordwall are proven to first activate students' affective dimension, building motivation and enthusiasm that subsequently serve as a foundation for deeper cognitive engagement. The findings of this review are expected to serve as evidence-based reference for teachers and policymakers in designing learning that is both effective and meaningful for students in the digital era.